Effect of retatrutide on body weight, lipid profile, liver function, oxidative stress, and inflammation in experimental obesity in male rats - AL-shibil, Zinah Meteab Rah; Kadhim, Zahraa J. (Rzeszów University Press, 2026)
Introduction and aim. Obesity is a global health concern associated with an increased risk of diabetes, cardiovascular disease, hypertension, and non-alcoholic fatty liver disease, often driven by chronic low-grade inflammation. Recent evidence suggests that retatrutide, a novel GIPR/GLP-1R/GCGR tri-agonist, possesses anti-inflammatory properties in addition to its known effects on glucose metabolism, lipid profiles, and weight reduction. However, comprehensive preclinical data on retatrutide’s direct impact on hepatic inflammation, oxidative stress, and FGF21 regulation in diet-induced obesity models remain limited. This study aims to investigate the potential protective effect of retatrutide on inflammatory and oxidative stress status in diet-induced obesity in male rats, thereby providing mechanistic insight into its hepatoprotective actions. Material and methods. Twenty-eight adult male Sprague-Dawley rats were randomly assigned to four groups: normal controls (standard chow for 12 weeks), obese controls (HF/sucrose diet for 12 weeks), vehicle-treated (HF/sucrose for 8 weeks, then normal saline S.C. for 4 weeks with HF/sucrose), and retatrutide-treated (HF/sucrose for 8 weeks, then retatrutide 25 nmol/kg S.C. for 4 weeks with HF/sucrose). Serum insulin, lipid profile, liver enzymes, blood glucose, and FGF21 were measured from blood samples. Crucially, tumor necrosis factor- α (TNF-α), malondialdehyde (MDA), and glutathione (GSH) levels were measured in liver tissue samples. Results. Modeling obesity using HF/sucrose diet significantly increased insulin levels, blood glucose, liver enzymes, lipid profile, serum FGF21, and body weight. It also considerably elevated hepatic MDA and TNF-α while reducing GSH levels. Retatrutide treatment resulted in significant improvements across most parameters compared to both the obesity and vehicle-treated groups (p<0.0001). Specifically, retatrutide-treated rats showed significant reductions in body weight (e.g., approximately 25% reduction compared to obese controls), blood glucose (e.g., from 107±5.944 mg/dL to 85.714±4.785 mg/dL), and liver enzymes AST (e.g., from 89.843±4.533 U/L to 48.959±4.816U/L) and ALP (e.g., from 168.451±28.384 U/L to 97.526±13.446 U/L). Lipid profile parameters, including cholesterol (e.g., from 232.325±23.058mg/dL to 105.881±26.225 mg/dL), triglycerides (e.g., from 112.140±11.450 mg/dL to 30.355±9.479 mg/dL), and LDL (e.g., from 171.557±17.678 mg/dL to 51.341±21.858 mg/dL), were significantly improved, while HDL (e.g., from 38.339±9.670 mg/dL to 65.759±13.828 mg/dL) was significantly increased. Hepatic inflammatory (TNF-α, e.g., from 115.621±5.682 pg/mL to 92.715±5.647 pg/mL) and oxidative stress markers (MDA, e.g., from 5.409±1.078 nmol/ml to 3.120±0.401 nmol/mL) were significantly reduced, and hepatic GSH levels (e.g., from 1.220±0.545 ng/mL to 2.895±0.475 ng/mL) were significantly increased, serum FGF21 (e.g. from 115.367±6.921 pg/mL to 87.445±4.279 pg/mL) . These parameters were largely restored to near-control levels in the retatrutide-treated group. Conclusion. This study assessed the hepatoprotective effect of retatrutide in a diet-induced obesity model. While the metabolic benefits of incretin-based therapies are well documented, data on retatrutide’s direct impact on liver-specific inflammatory and oxidative stress pathways remain limited. This study is among the first to simultaneously evaluate hepatic TNF-α, oxidative stress markers (MDA and GSH), and circulating FGF21 following retatrutide treatment in obese rats, thereby providing mechanistic insight into its hepatoprotective actions beyond weight loss and glycemic control.
The study followed the ARRIVE 2.0 guidelines for reporting animal experiments and complied with ethical standards. Approval was obtained from the Institutional Animal Care and Use Committee (IACUC) at the University of Kufa, Iraq, following the submission of the required documentation (NO. 2121) on January 23, 2025.
Keywords: inflammation; liver; obesity; retatrutide; weight loss